A review of the effects of different parameters on salt-based solar thermal energy storage systems - Kumar, Anil; Maithani, Rajesh; Sharma, Sachin; Alam, Tabish; Gupta, Naveen Kumar; Deifalla, Ahmed Farouk (Frontiers in Energy Research, 2023)
Phase change materials (PCMs) used for thermal energy storage (TES) have shown to be particularly promising, especially in light of the growing need for a wide variety of energy-related applications. This article discusses the usage of packed beds made from PCMs as a solar energy storage device for variable temperature environments. The primary heating/cooling technologies and associated TES difficulties have also been examined from the perspective of engineering applications. The packed bed's history from a thermodynamic perspective, the temperature dispersion inside the packed bed, and several design factors that influence its performance are all covered in the brief description of the packed bed. Energy and exergy efficacy are the foundations of its analysis. The article delves into numerous different thermal energy storage methods, with PCMs being the major topic and a beneficial means of storing thermal energy. In addition, PCMs may store latent thermal energy during phase transitions at almost constant temperatures.